Correlation of periodontitis during pregnancy and incidence of low birth weight babies - Prashanthi Reddy; Tushar Phulambrikar; P V Wanjari; Rajeev Srivastava (Wolters Kluwer Medknow Publications, 2012)
Objective: To verify a possible association between periodontitis and low birth weight babies. Materials and methods: Two hundred and eighty antepartum women were examined aged between 18 and 37 years. Demographic, medical and clinical histories were taken under obstetrician's guidance. A thorough periodontal examination was done in all the participants with their consent which included bleedina on Drobina. Docket death and clinical attachment level. After delivery, gestational age (in weeks) and birth weight of baby (in kg) were collected from hospital records. Infants were placed into following categories by gestational age (WHO) and by birth weight preterm-<37 weeks, term-37 to 42 weeks, post-term-42 weeks completed and above, low birth weight<2,500 gm, normal birth weight-2.500 to 3,900 gm, high ,weight->3,900 gm. Results: Based on the findings of the study, a significant correlation was observed between periodontitis and low birth weight and preterm low birth weight (p<_0.001) and a significant relation was observed between periodontitis and gestational age (p < 0.001). Conclusion: Periodontitis was considered a risk indicator for reduced gestational age and birth weight. Multicentric trials will greatly help to establish the independent role of periodontal disease and their relationship in terms of pregnancy outcomes.